THE OCCURRENCE OF INSECTS AND MOULDS IN STORED COCOA BEANS AT SOUTH SULAWESI - OKKY S. DHARMAPUTRA (SEAMEO BIOTROP, 1999)
Surveys on postharvest handling and technology processing of cocoa beans at farmer, trader and exporter levels in South Sulawesi were conducted together with investigations on moisture content, pest infestation (insect and mould) and quality characteristics in terms of reducing sugar, free amino acid and free fatty acid content. Surveys were conducted during dry (July 1997) and wet seasons (February 1998) in three regencies (Pinrang, Polewali-Mamasa and Luwu) and Ujung Pandang, South Sulawesi province. Interviews were carried out during surveys in the dry season. Number of respondents from farmers, trailers and exporters was 38, 15 and 5, respectively. In each season, number of samples taken from farmers, traders and exporters was 9, 21 and 15, respectively. In general, farmers, traders and exporters did not carry out postharvest handling and technology processing properly. MoistureÂ content of cocoa beans collected from farmers, traders and exporters were higher than the tolerable limit recommended by SNI (7.5%). Moisture content of cocoa beans collected during the wet season was higher than in the dry season. Insects were found on cocoa beans collected from traders and exporters. Species composition and the presence of each insect species were varied among the two seasons, but the predominant species was Tribolium castaneum. At trader level the percentage of insect-damaged beans during the wet season was higher than that during the dry season, while at exporter level it was lower. During the two seasons the percentage of mouldy beans at farmer level was lower than the tolerable limit recommended by SNI (4%), while those from some samples at trader and exporter levels were higher than 4%, but based on the direct plating method, all of the samples at trader and exporter levels were mouldy. Species composition and the percentage of beans infected by each mould species at farmer, trader and exporter levels during the two seasons were varied. The percentage of mouldy beans increased at trader and exporter levels. The predominant moulds were Aspergillus flaws, Eurotium amstelodami, E. chevalieri and Penicillium citrinum. The predominant mould at farmer level during wet season was Saccharomyces cerevisiae (yeast). Reducing sugar and free amino acid content of cocoa beans collected during the dry season was higher than those collected during the wet season, either at farmer, trader or exporter levels. Free fatty acid content of cocoa beans tends to be higher during the wet season than the dry season at the three levels.Keywords: Stored products pests/Postharvest handling/Technology processing/Moisture content/In-sect/Mould/Reducing sugars/Free amino acids/Free fatty acids/Cocoa/South Sulawesi.